Characterization of Sulfurimonas hydrogeniphila sp. nov., a Novel Bacterium Predominant in Deep-Sea Hydrothermal Vents and Comparative Genomic Analyses of the Genus Sulfurimonas - Wang, Shasha; Jiang, Lijing; Hu, Qitao; Cui, Liang; Zhu, Bitong; Fu, Xiaoteng; Lai, Qiliang; Shao, Zongze; Yang, Suping (Frontiers in Microbiology, 2021)
Bacteria of the genus Sulfurimonas within the class Campylobacteria are predominant in global deep-sea hydrothermal environments and widespread in global oceans. However, only few bacteria of this group have been isolated, and the mechanisms underlying their adaptations to these harsh environments remain poorly understood. Here, we report a novel mesophilic, hydrogen- and sulfur-oxidizing bacterium, strain NW10T, isolated from a deep-sea sulfide chimney of Northwest Indian Ocean. 16S rRNA gene sequence analysis showed that strain NW10T was most closely related to the vent species Sulfurimonas paralvinellae GO25T with 95.8% similarity, but ANI and DDH values between two strains were only 19.20% and 24.70%, respectively, indicating that strain NW10 represents a novel species. Phenotypic characterization showed strain NW10T is an obligate chemolithoautotroph utilizing thiosulfate, sulfide, elemental sulfur or molecular hydrogen as energy sources, carbon dioxide as the sole carbon source, and with molecular oxygen, nitrate or elemental sulfur as electron acceptors. Moreover, hydrogen supported a better growth than reduced sulfur compounds. During thiosulfate oxidation, the strain can produce extracellular sulfur of elemental α-S8 with an unknown mechanism. Polyphasic taxonomy results support that strain NW10T represents a novel species of the genus Sulfurimonas, and named as Sulfurimonas hydrogeniphila sp. nov. Genome analyses revealed its diverse energy metabolisms driving carbon fixation via rTCA cycling, including pathways of sulfur/hydrogen oxidation, coupled oxygen/ sulfur respiration and denitrification. Comparative analysis of the 11 available genomes from Sulfurimonas species revealed that vent bacteria, compared to marine non-vent strains, possess unique genes encoding Type V Sqr, Group II and Coo hydrogenase, and are selectively enriched in genes related to signal transduction and inorganic ion transporters. These phenotypic and genotypic features of vent Sulfurimonas may explain their thriving in hydrothermal environments and help to understand the ecological role of Sulfurimonas bacteria in hydrothermal ecosystems.